Mapping the landscape of the business model and open innovation scientific field to set proposals for directions of future research - Adam Ryszko; Marek Szafraniec (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
In recent years increasing attention has been paid to theory building and empirical research that explore the links between the business model and open innovation (BM&OI). Nevertheless, studies presenting the results of bibliometric analyses merging these two terms are still scarce. Therefore, the main aim of this paper was to present the results of a comprehensive bibliometric analysis focused on the determination and mapping of the evolving cognitive and social structures in the BM&OI literature to set proposals for directions of future research. Our research was based on the dataset obtained from the Scopus database and made use of the Biblioshiny and the VOSviewer software. Descriptive and network analyses were conducted to demonstrate an overview of the scientific field under consideration. We identified the leading authors, sources, countries and institutions in the BM&OI literature. The most influential publications on the BM&OI and the most cited references by documents covering the BM&OI research were indicated. Based on the thematic evolution and thematic maps, the evolving structures of key sub-fields of the BM&OI research were determined and discussed. Moreover, the major clusters and the specificity of scientific collaboration in the analyzed research domain were identified and described. Our intention was to demonstrate to both scholars and practitioners the wide-ranging landscape of multifaceted research on the BM&OI.
Keywords: 650; business model; open innovation; bibliometric analysis; network analysis